Controlling lungworm disease (husk) in dairy cattle. Issue 9 (18th September 2017) - McLeonard, Catherine; van Dijk, Jan
Abstract : Vaccination and anthelmintic (preventive) treatments for the control of the bovine lungworm Dictyocaulus viviparus have been available for some time. However, the number of outbreaks experienced has remained high, with clinical disease in adult cattle often causing particularly dramatic, milk yield‐associated, losses. This article provides an update on pasture epidemiology, including immunity, the use of vaccination, the diagnostic tests available and the pitfalls to performing these tests. It also discusses how lungworm and gutworm control can be amalgamated, as well as some key risk factors and possible solutions to outbreaks of lungworm in dairy herds.